2019
DOI: 10.5468/ogs.2019.62.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Positive culture rate and antimicrobial susceptibilities of Mycoplasma hominis and Ureaplasma urealyticum

Abstract: ObjectiveTo assess positive culture rate and antimicrobial susceptibilities of Mycoplasma hominis (MH) and Ureaplasma urealyticum (UU) in symptomatic general population and pregnant women admitted with preterm labor and premature rupture of membranes.MethodsWe retrospectively reviewed medical records of patients who have undergone culture test and antimicrobial susceptibilities at our center from January 2017 to April 2018. Patients with positive culture for MH, UU, or both were included in this study.ResultsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
2
12
0
2
Order By: Relevance
“…According to several studies conducted in South Korea, the prevalence of Ureaplasma species in symptomatic patients was higher than that of M. hominis . The prevalence of Ureaplasma species and M. hominis was 21.3% and 2.9%, as reported by Moon et al ( 8 ), 65.6% and 11.8% by Kweon et al ( 9 ), and 48.8% and 25.3% by Jang et al ( 10 ), respectively. Similar values were reported in Poland ( 11 ) and China ( 12 ).…”
Section: Discussionsupporting
confidence: 71%
“…According to several studies conducted in South Korea, the prevalence of Ureaplasma species in symptomatic patients was higher than that of M. hominis . The prevalence of Ureaplasma species and M. hominis was 21.3% and 2.9%, as reported by Moon et al ( 8 ), 65.6% and 11.8% by Kweon et al ( 9 ), and 48.8% and 25.3% by Jang et al ( 10 ), respectively. Similar values were reported in Poland ( 11 ) and China ( 12 ).…”
Section: Discussionsupporting
confidence: 71%
“…MH infection and UU+MH mixed infection were resistant to clarithromycin, roxithromycin, azithromycin, ofloxacin, and levofloxacin. This is because MH has multiple drug resistance genes, natural resistance to most macrocyclic ester drugs, and cross-resistance to quinolones (13). In this study, the sensitivities of doxycycline, minocycline, and josamycin were over 95%, while the resistance of ofloxacin, levofloxacin, and azithromycin were over 20%, which indicated that appropriate antibiotics should be selected for different types of Mycoplasma.…”
Section: Discussionmentioning
confidence: 71%
“…Змішані інфекції становлять значну частину всіх випадків інфекційних захворювань генітального тракту, причому відзначається поєднання 3-х і більше збудників. Літературні дані свідчать про збільшення частоти виявлення мікробних асоціацій в ослаблених пацієнтів із хронічними захворюваннями статевих органів [8,9].…”
Section: акушерство та гінекологіяunclassified